Transformational Leadership of Islamic School Principals: A Literature Review - Joko Triyantoro; Bujang Rahman; Sowiyah Sowiyah; Hasan Hariri; Diah Ayu Sucitra (Universitas Muhammadiyah Enrekang, 2024)
The transformational leadership of Islamic-based school principals integrates Islamic teaching values ​​such as justice, trust, and responsibility in carrying out leadership roles. This research uses a literature review method, where data was collected through articles from 2018 to 2024. There are 16 articles that are references from Google Scholar. The research results show that leadership with secular and spiritual concepts, achieves important goals beyond organizational goals while leadership requires high commitment towards Islam, establishing principles, and leadership is not just a responsible humanitarian task. This article can be useful from a theoretical perspective, namely to increase knowledge about Islamic-based transformational leadership. Then it can be used as a reference for subsequent research.